Zum Zusammenhang zwischen Employer Awards und Arbeitgeberattraktivität - Stephan Weinert (Hochschule Düsseldorf, Fachbereich Wirtschaftswissenschaften, 2017)
In der vorliegenden Studie wurde der Forschungsfrage nachgegangen, ob Unternehmen in Employer Awards investieren sollten, um als attraktiver Arbeitgeber wahrgenommen zu werden. Methodisch basiert die Untersuchung auf einem experimentellen einfaktoriellen Zufallsgruppenversuchsplan mit Mehrgruppen-Design. Der zentrale Befund lautet, dass Unternehmen Investitionen in Employer Awards kritisch prüfen sollten, da von ihnen kein positiver Effekt auf die wahrgenommene Arbeitgeberattraktivität auszugehen scheint. @The study's research question was if firms should invest in employer awards in order to be better perceived as attractive employers. The methodology was based on an experimental univariate randomized multi-group design. As a main finding it can be concluded that firms should carefully evaluate if investments in employer awards are necessary, given that they seem not to have any positive effect on perceived employer attractiveness. – – The study's research question was if firms should invest in employer awards in order to be better perceived as attractive employers. The methodology was based on an experimental univariate randomized multi-group design. As a main finding it can be concluded that firms should carefully evaluate if investments in employer awards are necessary, given that they seem not to have any positive effect on perceived employer attractiveness.
urn:nbn:de:hbz:due62-opus-10676
Keywords: 650; Employer Branding; Employer Awards; Recruiting